2017
DOI: 10.3389/fphar.2017.00319
|View full text |Cite
|
Sign up to set email alerts
|

Gliotoxin Targets Nuclear NOTCH2 in Human Solid Tumor Derived Cell Lines In Vitro and Inhibits Melanoma Growth in Xenograft Mouse Model

Abstract: Deregulation of NOTCH2 signaling is implicated in a wide variety of human neoplasias. The current concept of targeting NOTCH is based on using gamma secretase inhibitors (GSI) to regulate the release of the active NOTCH intracellular domain. However, the clinical outcome of GSI remains unsatisfactory. Therefore we analyzed human solid tumor derived cell lines for their nuclear NOTCH activity and evaluated the therapeutic potential of the NOTCH2 transactivation inhibitor gliotoxin in comparison to the represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 49 publications
0
19
0
1
Order By: Relevance
“…Although this study did not explore the mechanisms underlying the observed antiproliferative activity, there are many other reports on gliotoxin cytotoxic properties revealing a multifaceted signaling pathway linked to their activity against different cancer cells [123][124][125]. This molecule has demonstrated potential in targeting the Wnt/β-catenin pathway [123], farnesyltransferase and geranylgeranyltransferase [126], and the NOTCH2 [125,127]. Besides, gliotoxin was shown to activate JNK and Bim-mediated apoptosis through a RhoA-ROCK-MKK4/MKK7-dependent pathway [128] and to exert antiangiogenic activity through disruption of the HIF-1α/p300 complex in prostate cancer cell lines and xenograft models [129].…”
Section: Further Accessing Brazilian Marine Environments: Studies Witmentioning
confidence: 88%
“…Although this study did not explore the mechanisms underlying the observed antiproliferative activity, there are many other reports on gliotoxin cytotoxic properties revealing a multifaceted signaling pathway linked to their activity against different cancer cells [123][124][125]. This molecule has demonstrated potential in targeting the Wnt/β-catenin pathway [123], farnesyltransferase and geranylgeranyltransferase [126], and the NOTCH2 [125,127]. Besides, gliotoxin was shown to activate JNK and Bim-mediated apoptosis through a RhoA-ROCK-MKK4/MKK7-dependent pathway [128] and to exert antiangiogenic activity through disruption of the HIF-1α/p300 complex in prostate cancer cell lines and xenograft models [129].…”
Section: Further Accessing Brazilian Marine Environments: Studies Witmentioning
confidence: 88%
“…Moreover, transformed cells may express truncated NOTCH forms that do not depend on γ-secretase for processing and function [49,50]. A search for an alternative to GSI revealed that the Aspergillum-derived secondary metabolite gliotoxin is a potent inhibitor of DNA-bound NOTCH2/CSL transcription factor complexes, and efficiently induced apoptosis in CLL lymphocytes and in NOTCH2-associated solid tumor cell lines-independent of their sensitivity to GSIs [32,51] In this study, we show that gliotoxin as a nuclear NOTCH2 inhibitor may have an additional therapeutic advantage over GSI as pan-NOTCH inhibitors in CLL. We were able to demonstrate that the GSI RO4929097 targets an unexpected non-canonical tumor-suppressing NOTCH3 activity, which is involved in spontaneous as well as gliotoxin-induced apoptosis in CLL cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transformed cells may express truncated NOTCH forms that do not depend on γ-secretase for processing and function [ 49 , 50 ]. A search for an alternative to GSI revealed that the Aspergillum -derived secondary metabolite gliotoxin is a potent inhibitor of DNA-bound NOTCH2/CSL transcription factor complexes, and efficiently induced apoptosis in CLL lymphocytes and in NOTCH2-associated solid tumor cell lines—independent of their sensitivity to GSIs [ 32 , 51 ]…”
Section: Discussionmentioning
confidence: 99%
“…Experimental animal models also proved to be reliable sources of data concerning (i) the screening for novel antimelanoma agents: temozolomide (B16F10 metastatic melanoma model) [ 66 , 67 ], thymoquinone (B16F10 intracerebral melanoma model using C57BL/6J mice as host) [ 68 ], oncolytic herpes simplex virus HF10, and dacarbazine combined therapy (DBA/2 mice subcutaneously inoculated with clone M3 mouse melanoma cells) [ 69 ], gliotoxin (a xenograft mouse model using athymic mice) [ 70 ], recombinant methioninase [ 71 ], cancer vaccines [ 72 ], natural compounds [ 73 , 74 ]; (ii) molecular discovery—the comprehension of melanoma metastatic pathway involving microvascular environment [ 75 ]; and (iii) in vivo tracing of melanocytic lineage cells [ 76 ].…”
Section: Murine Models Of Melanomamentioning
confidence: 99%